Effects of δ Phase and Annealing Twins on Mechanical Properties and Impact Toughness of L-PBF Inconel 718 - Wakshum Mekonnen Tucho; Bjorn Andre Ohm; Sebastian Andres Pedraza Canizalez; Andreas Egeland; Martin Bernard Mildt; Mette Lokna Nedreberg; Vidar Folke Hansen (Journal of Manufacturing and Materials Processing, 2024)
In this study, the effects of the δ phase and annealing twins on the hardness, tensile properties, and Charpy impact toughness of Inconel 718 fabricated using L-PBF were investigated. The as-printed components underwent two stages of heat treatment to modify their microstructure and phases. The δ phase was induced through solid-solution heat treatment at 980 °C for 1 h, while annealing twins were formed at 1100 °C for 3 h. Following precipitation hardening, specimens containing δ precipitates exhibited a higher ultimate tensile strength (13%), yield strength (27%), and hardness (12%) compared to those rich in annealing twins. The enhanced mechanical strength was attributed to the presence of δ precipitates and differences in the extent of recrystallization, leading to variations in the density of retained lattice defects, including subgrain boundaries and primary phases. Conversely, specimens with annealing twins demonstrated a significantly higher impact toughness (four times) and ductility (twice) than those with δ precipitates. Annealing twins were found to enhance plasticity by impeding dislocation movement, while δ precipitates reduced plasticity by acting as sites for void formation and crack propagation. Microstructural, compositional, phase, crystallographic, and fractographic analyses were conducted using OM, SEM, TEM, and XRD techniques to identify the factors influencing the observed differences. The results indicate that the heat treatment approach involving annealing twins can effectively enhance the ductility of Inconel 718 while maintaining the necessary mechanical strength.